2020
DOI: 10.3390/ijerph17072550
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality and Medical Burden of Patients with Chronic Obstructive Pulmonary Disease with and without Subsequent Stroke Episodes

Abstract: Background: We used the Taiwan National Health Insurance Research Database (NHIRD) to determine the differences in mortality and medical burden between patients with chronic obstructive pulmonary disease (COPD) with and without stroke. Methods: We enrolled participants aged ≥20 years and defined four subgroups in this study, namely patients with COPD (International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9 CM): 491, 492, 494, and 496), patients with COPD with stroke (ICD-9 CM: 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Our finding that COPD is positively associated with increased risk of in-hospital and long-term mortality is consistent with those of some previous studies [19, 20]. However, one retrospective study [10] found that COPD was not significantly associated with stroke severity at hospital admission nor with short-term outcome in stroke patients but only with long-term mortality during follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that COPD is positively associated with increased risk of in-hospital and long-term mortality is consistent with those of some previous studies [19, 20]. However, one retrospective study [10] found that COPD was not significantly associated with stroke severity at hospital admission nor with short-term outcome in stroke patients but only with long-term mortality during follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been described by other authors. 25 Several factors may explain the increased mortality risk among patients with COPD. They include comorbid conditions that can be associated with increased mortality, 26 increased risk of dysphagia, that may predispose to the development of aspiration pneumonia in these patients, 27 gas exchange disturbances (hypoxemia and hypercapnia) and inflammation and oxidative stress during exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study also suggested that affected populations with more co-morbidities (i.e., liver cirrhosis, CKD, COPD, asthma and neoplasms other than cardiovascular disease) have higher all-cause mortality hazards. The increased all-cause mortality occurred when patients with multimorbidity and pre-existing cardiovascular diseases such as stroke and ischemic heart diseases had increased risk of complications from either underlying diseases or comorbidities [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%